Philosophy of Education in Times of Crises and Pandemics - Marianna Papastephanou (MDPI AG, 2021)
In much of the philosophy of education today, diagnoses of socio-political pathologies underpin visions of a more desirable, democratic future. However, the very philosophical act of making an educational vision responsive to (and dependent on) crises of the times is rarely, if ever, critiqued. On the contrary, a pattern of standardised research steps is being consolidated, one that reflects medicalised politics of identifying a critically "ill" present, offering "cures" that promise a better future. In this article, it is argued that this pattern has major epistemic and political risks. It may jeopardise the quality of educational-philosophical research, and it may make philosophy of education overlook new, undemocratic politics. This article briefly discusses the pattern, and then the risks of the medical metaphors on which the pattern relies. One such risk concerns what counts as politically "ill" in "pandemic times", and new polarisations, such as "the vaccinated versus the unvaccinated", may thus be introduced. Finally, the article suggests that philosophy of education should consider some de-medicalisation of the notion of pandemics.